2014
DOI: 10.1007/s11192-014-1393-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact analysis of domestic and international research collaborations: a Malaysian case study

Abstract: This paper presents a comparative impact analysis on collaborative research in Malaysia. All analyses were conducted using ISI-indexed journal articles published in the 10-year period spanning the years 2000-2009. The publication growth and distribution of domestic versus international Malaysian-addressed collaborative articles was examined. Then, a three-pronged approach was used to compare the research performance between international and domestic research for the top ten high-productivity subject categorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…The association between the variables "international co-authorship" and "citations" proven in other contexts by Glänzel and Schubert [6], Persson et al [19] and Tan et al [20], was also moderate in our data, reaching a value of 0.235, which is very similar to the previous result for references. Although the correlation is modest and other studies have identified stronger associations, the results confirm the hypothesis that international collaboration influences the number of citations received by articles.…”
Section: National and International Co-authorshipsupporting
confidence: 91%
“…The association between the variables "international co-authorship" and "citations" proven in other contexts by Glänzel and Schubert [6], Persson et al [19] and Tan et al [20], was also moderate in our data, reaching a value of 0.235, which is very similar to the previous result for references. Although the correlation is modest and other studies have identified stronger associations, the results confirm the hypothesis that international collaboration influences the number of citations received by articles.…”
Section: National and International Co-authorshipsupporting
confidence: 91%
“…Additionally, some research papers were reported associated with the relationship between R&D management and technology innovation. Tan et al ( 2015 ) presented a comparative impact analysis on collaborative research in Malaysia using journal articles published in the 10-year period spanning, the years 2000–2009. Bacchiocchi and Montobbio ( 2009 ) estimated the process of diffusion and decay of knowledge from university, public laboratories and corporate patents.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…[14] There are many studies in Malaysia on Scientometric research too. These were focused on several subject area as well as other area such as computer science, [15] Engineering, [16] Clinical, [17] Medicine, [18] Library and Information Science (LIS), [19] Malaysia's journal, [20,21] collaboration research, [22] research productivity by returnees, [23] citation analysis, [24] ethnic research [25] and toxicology. [26] There are alsostudies conducted by Ministry of Science, Technology and Innovation (MOSTI) about the research productivity periodically.…”
Section: Introductionmentioning
confidence: 99%